LITS: tracking Botswana's livestock using radio waves - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Tinus Burger describes the Livestock Identification Trace-back System (LITS) project in Botswana. LITS employs radio frequency identification (RFID) technology to capture data on individual cattle, which is transmitted directly, error-free, to a central d